The Carboxy-terminus of BAK1 regulates kinase activity and is required for normal growth of Arabidopsis - Oh, Man-Ho; Wang, Xuejun; Kim, Sang Y.; Wu, Xia; Clouse, Steven D.; Huber, Steven C. (Frontiers in Plant Science, 2014)
Binding of brassinolide to the brassinosteroid-insenstive 1(BRI1) receptor kinase promotes interaction with its co-receptor, BRI1-associated receptor kinase 1 (BAK1). Juxtaposition of the kinase domains that occurs then allows reciprocal transphosphorylation and activation of both kinases, but details of that process are not entirely clear. In the present study we show that the carboxy (C)-terminal polypeptide of BAK1 may play a role. First, we demonstrate that the C-terminal domain is a strong inhibitor of the transphosphorylation activity of the recombinant BAK1 cytoplasmic domain protein. However, recombinant BAK1 lacking the C-terminal domain is unable to transactivate the peptide kinase activity of BRI1 in vitro. Thus, the C-terminal domain may play both a positive and negative role. Interestingly, a synthetic peptide corresponding to the full C-terminal domain (residues 576–615 of BAK1) interacted with recombinant BRI1 in vitro, and that interaction was enhanced by phosphorylation at the Tyr-610 site. Expression of a BAK1 C-terminal domain truncation (designated BAK1-ΔCT-Flag) in transgenic Arabidopsis plants lacking endogenous bak1 and its functional paralog, bkk1, produced plants that were wild type in appearance but much smaller than plants expressing full-length BAK1-Flag. The reduction in growth may be attributed to a partial inhibition of BR signaling in vivo as reflected in root growth assays but other factors are likely involved as well. Our working model is that in vivo, the inhibitory action of the C-terminal domain of BAK1 is relieved by binding to BRI1. However, that interaction is not essential for BR signaling, but other aspects of cellular signaling are impacted when the C-terminal domain is truncated and result in inhibition of growth. These results increase the molecular understanding of the C-terminal domain of BAK1 as a regulator of kinase activity that may serve as a model for other receptor kinases.